2015
DOI: 10.5056/jnm14084
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corticotropin-releasing Factor in Gastrointestinal Permeability

Abstract: The interface between the intestinal lumen and the mucosa is the location where the majority of ingested immunogenic particles face the scrutiny of the vast gastrointestinal immune system. Upon regular physiological conditions, the intestinal microflora and the epithelial barrier are well prepared to process daily a huge amount of food-derived antigens and non-immunogenic particles. Similarly, they are ready to prevent environmental toxins and microbial antigens to penetrate further and interact with the mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
80
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 203 publications
(187 reference statements)
2
80
0
5
Order By: Relevance
“…6,34 Glucocorticoids play a role in the increased intestinal permeability induced by a short acute maternal separation stress in PND10 pups 17 but not in adult rats subjected to repeated maternal separation. 36,37 In the present study, we found no correlation between corticosterone plasma levels and intestinal permeability at weaning, either in LNS or BMS models, suggesting that glucocorticoids are not involved in the mechanisms contributing to the altered permeability. Peripheral corticotropin-releasing factor receptors and nerve growth factors have been identified as major underlying mechanisms of the enhanced intestinal permeability in adult rats exposed to intermittent maternal separation post-natally.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…6,34 Glucocorticoids play a role in the increased intestinal permeability induced by a short acute maternal separation stress in PND10 pups 17 but not in adult rats subjected to repeated maternal separation. 36,37 In the present study, we found no correlation between corticosterone plasma levels and intestinal permeability at weaning, either in LNS or BMS models, suggesting that glucocorticoids are not involved in the mechanisms contributing to the altered permeability. Peripheral corticotropin-releasing factor receptors and nerve growth factors have been identified as major underlying mechanisms of the enhanced intestinal permeability in adult rats exposed to intermittent maternal separation post-natally.…”
Section: Discussionmentioning
confidence: 50%
“…Peripheral corticotropin-releasing factor receptors and nerve growth factors have been identified as major underlying mechanisms of the enhanced intestinal permeability in adult rats exposed to intermittent maternal separation post-natally. 36,37 Whether similar mechanisms are implicated in the increased permeability during the developmental period at weaning need to be further investigated. Intestinal barrier disruption has been described to occur in IBS patients, [38][39][40][41] although the link between early adverse life events and increased intestinal permeability needs to be evaluated based on the present experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In contrast, activation of CRF-R2 by administration of CRF-R2 agonist can prevent visceral pain induced by colorectal distention. 24 With respect to the relationship between these two receptors, it has been reported that CRF-R1 is the primary receptor involved in stress-induced alterations of lower gut secretomotor and pain sensations, whereas CRF-R2 regulates the CRF-R1-mediated stimulation of intestinal motor function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the corticotrophin-releasing factor, a key modulator of stress response in the brain, has been extensively investigated and the present role in the gastrointestinal tract such as decreasing gastric emptying, increasing colonic motility, and inducing visceral hypersensitivity are established. [2][3][4] Psychological comorbidities such as depression and anxiety are also more prevalent in patients with IBS compared to healthy controls and is thought to play an important role in IBS.…”
mentioning
confidence: 99%
“…For example, the corticotrophin-releasing factor, a key modulator of stress response in the brain, has been extensively investigated and the present role in the gastrointestinal tract such as decreasing gastric emptying, increasing colonic motility, and inducing visceral hypersensitivity are established. [2][3][4] Psychological comorbidities such as depression and anxiety are also more prevalent in patients with IBS compared to healthy controls and is thought to play an important role in IBS.1 However, latest medical and scientific developments have led to further investigation of organic changes in patients with IBS such as inflammatory cell infiltration, increased permeability, and changes in neuroendocrine system in the gut. 5,6 The enteric nervous system (ENS) is one of the candidates for a possible organic cause of underlying IBS pathophysiology.…”
mentioning
confidence: 99%